Village Existence in the Constitutional Framework: Orientation and Formulation in the Perspective of Integrative Law - RS, Iza Rumesten; Muntaqo, Firman; Adisti, Neisa Angrum (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
According to the provisions of the constitution, the village government does not actually have adequate arrangements as can be seen from the fact that the term village or something similar to it has not been accommodated in the Indonesian constitution. Orientation of village government arrangements in the constitution and efforts to formulate village government arrangements in the constitution with an integrative legal perspective. Normative legal research with a concept and statutory approach. The orientation of village arrangements in the constitution is intended to reinforce and facilitate democracy and local village leadership which is the style and identity of each village based on traditional rights and rights of origin. The formulation of integrative law so that the substance of the village government can obtain a strong legal position in the constitution, which can be done by conducting hearings or polling the aspirations of the community, efforts are needed to revise the Village Law with a pluralistic character, which means facilitating various types of village government that already exist.